Exploratory Study on History Education and the Construction of Patriotism Among the Youth in Malaysia - Abd Wahab, Amelia Yuliana; Jamil, Hare; Razak, Abdul Rahman Abdul; Shuib, Munir (International Journal of Psychosocial Rehabilitation, 2020)
This study explores the importance of history education towards the construction of patriotism in a multiethnic society in Malaysia. The discussion is based on the experiences and views from the youth in the state of Johor Bahru, Peninsula Malaysia. A qualitative methodology using a phenomenology approach is used to gain insight from the thirty informants. There are four themes discussed which include informants’ experience in learning history in school, expression of ‘love’ as Malaysians, understanding on the Independence and ‘making of Malaysia’ and lastly, the informants’ views on the common Malaysian identity in a multiethnic society. The findings emphasize the critical role of schools and higher education institutions in instilling the patriotic spirit through history education.